Mediastinal Hepatoid Adenocarcinoma Treated With Arterial Interventional Therapy: A Case Report and Review of Literature - Zhang, Guiyuan; Wen, Chunyong; Chen, Bin; Dai, Haitao; Lin, Run; Huang, Yonghui; Xiang, Xianhong (Frontiers in Oncology, 2022)
Hepatoid adenocarcinoma (HAC) is an extremely rare mediastinal carcinoma, which is pathologically featured by hepatocellular carcinoma (HCC) and marked by producing alpha-fetoprotein (AFP). HAC of mediastinum is extremely rare. For inoperable patients, the curative treatment options have not been established, the outcome of HAC is usually poor. Herein, we present a case of mediastinal HAC with normal serum AFP level who achieved well-controlled and good response after local-regional interventional approach combined with systemic PD-1 inhibitor. A 53-year-old male complained with chest pain was admitted to our hospital in February 2021. Chest CT scan revealed several tumors in his mediastinum. The laboratory data showed normal serum AFP level. HAC was diagnosed through pathological assessment of biopsy. Surgery was not available due to the infiltration of sternum. Local regional FOLFOX chemotherapy was given by transarterial infusion, followed by transcatheter arterial chemoembolization, and thereafter combined with systemic anti-PD-1 treatment. The patient achieved favorable disease control and apparent symptom relief. So transarterial interventional therapy combined immunotherapy may be a possible and promising treatment for mediastinal HAC.